Peran Program Karawang Berseri dalam Upaya Pemberdayaan Masyarakat, Pencegahan dan Penanganan Kekerasan Terhadap Perempuan dan Anak - Wazirul Luthfi; Iftitahur Rohmah; Diaz Alvin Firdausa; Annisa Nur Fadhillah (Jurnal Syntax Admiration, 2023)
The increased recognition of the significance of sustainable development has led business communities in Indonesia to fulfill Corporate Social Responsibility (CSR). One example is the implementation of a corporate social responsibility program by PT Pertamina EP Zone 7 Tambun Field which focuses on efforts to eradicate violence against women and children in Karawang, known as "Karawang Berseri" or "Karawang Free from Violence, Growing and Independent". This research will analyze the implementation of the Karawang Berseri program from the perspective of community empowerment, starting from planning, implementation, and ultimately generating impacts and benefits for the community, especially in Karawang Kulon Sub-District. This research uses a qualitative approach to literature sources related to the program. The Karawang Berseri Program has had a positive impact not only in dealing with the problem of violence against women and children, but also in seeking program sustainability by creating an independent source of financing from hydroponic cultivation activities and joint economic initiatives. The effectiveness of the program is also supported by innovations through the program such as redesigning the case-handling system, standardization of networking service procedure, creation of a Desa Berseri Module, and the Gender School Discussion Series. Apart from that, participation from the local community is the main key in the sustainable success of the Karawang Berseri program because they are involved as beneficiaries and implementers of activities, so they are independently motivated. The achievements of the Karawang Berseri program have proven a successful and sustainable model of community empowerment in overcoming the problem of violence against women and children.